Estudio sobre el manejo de antibióticos en hatos lecheros artesanales de Costa Rica - Luna Tortós, Carlos (2006)
Between 35-40% of the milk(fluid ir as cheese)  consumed by costarican population is produced in tradicional farms. Taken into account that this milk is not evaluated  for residues of  antibiotics, and that this fact represent an important problem for the public health, we carried out a survey on the use of antibiotics in a region with traditional farming. The primary objective of this study was to determine management practices concerning drugs use, mainly those related to the withdrawal period and withholding time. The survey was conducted on 60 dairy farms. The design included the standarized questionnaire was gathered during a farm visit. In 90% of farms, penicillin G with dihydrostreptomycin were used to treat diseases, followed by oxytetracycline, which were used in 72% of the farms. To treat clinical mastitis, 90% of the farmers use procaine penicillin G with dihydrostreptomycin,  27% use an intramammary combination  which include oxytetracycline, neomycin, bacitracin, prednisolone and 8% of the farmers use cefoperazone. In 43% of the farms, Pencillin G  in combination with dihydrostreptomycin, neomicin and hidrocortizone were used for dry-cow therapy. In 35% of the farms, Cloxacillin alone or in combination with ampicillin were also used for dry-cow therapy. 68% of the farmers use intramammary antibiotics, however they do not discard milk from all quarters, 53% of the farmers treat subclinical mastitis during the lactation and the milk is not withheld until the end of the recommended withdrawal period. 75% of the producers mentioned that they always takes into account the withdrqwal period for the drug being used. However many other management practices present in this farms could increase the risk of antibiotic residues in milk, because of the following reasons: preparations with a slow-realising base are used in dry-cow therapy without taking into account the long of dry period; the use of  long acting antibiotics for treatment of several diseases but not withholding milk for the full withdrawall period. Another reason are, 15% of the farmers admited taht they sometimes transfer accidentally contaminated milk, 80% of the famers have no records, 92% never identify treated cows at all, half of the priducers do not separate treated cows from untreated while milking and 58% of the farmers recognized that they discard the milk of cows geind treated for pospartal diseases only if antibiotics are given parenteral but not when they are intrauterine. Also was found that only 38% of the farmers recognize that antibiotics residues in milk is a public health risk. This study shows that there is a high hazard  of antibiotic residues in the milk and dairy products of this farms. Therefore health authorities should pay atention to this important issue of public health.